2006
DOI: 10.1207/s15327914nc5501_4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Low-Fat, High-Fiber Diet and Exercise Program on Breast Cancer Risk Factors In Vivo and Tumor Cell Growth and Apoptosis In Vitro

Abstract: Abstruct: The present study irwestigated the effects of a diet and exercise intervention on known breast cancer (BCa) risk factors, including estrogen, obesity, insulin, and insulin-like growth factor-I QGF-I), in overweight/obese, postmenopausal women. In addition, using the subjects'pre-and postintervention serum in vitro, serum-stimulated growth and apoptosis of three estrogen receptor-positive BCa cell lines were studied. The women where placed on a low-fat (10-15% kcal), high-fber (30-40 gper 1,000 kcal/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 42 publications
1
47
1
3
Order By: Relevance
“…Finally, the possibility that dietary fat may affect iron bioavailability has been raised, and this issue requires further study [35]. The interaction between animal-derived iron and fats that we found may also partly explain the previously reported lack of significant reduction in breast cancer risk with reduction in dietary fat, despite evidence from in vitro studies that breast cancer risk factors can be impacted by low-fat, high-fiber diets [36,37]. Although the effect of dietary fat on breast cancer risk has been thought to be mediated through elevated estrogen levels, this hypothesis has remained controversial and does not explain why animal fats alone are associated with risk [31,38,39].…”
Section: Discussionmentioning
confidence: 83%
“…Finally, the possibility that dietary fat may affect iron bioavailability has been raised, and this issue requires further study [35]. The interaction between animal-derived iron and fats that we found may also partly explain the previously reported lack of significant reduction in breast cancer risk with reduction in dietary fat, despite evidence from in vitro studies that breast cancer risk factors can be impacted by low-fat, high-fiber diets [36,37]. Although the effect of dietary fat on breast cancer risk has been thought to be mediated through elevated estrogen levels, this hypothesis has remained controversial and does not explain why animal fats alone are associated with risk [31,38,39].…”
Section: Discussionmentioning
confidence: 83%
“…A similar approach was undertaken by Barnard et al (2), who conducted studies with obese postmenopausal subjects and collected serum 24 h after the exercise intervention. In these studies, the exercise intervention was combined with a low-fat, high-fiber diet for 2 wk, and thus the effect of the metabolic profile in the serum caused by the diet or exercise intervention could not be differentiated.…”
Section: E507 Exercise-conditioned Serum Inhibits Tumor Cell Growthmentioning
confidence: 99%
“…Recently, it was shown that conditioned media from electrostimulated C 2 C 12 muscle cells could inhibit mammary cancer cell proliferation (3), suggesting that the contracting myotubes release humoral factors that can inhibit cancer cell growth. In continuation, Barnard et al (2) have shown that serum obtained from subjects after 2 wk of a low-fat, high-fiber diet and exercise intervention could inhibit mammary cancer cell growth in vitro. Similar interventions in men were shown to inhibit prostate cancer cell proliferation (25).…”
mentioning
confidence: 98%
“…Dietary fiber increases the fecal excretion of estrogen [11] and binds estradiol [12] thereby reducing bio-available levels; and most studies in humans have found that estrogen levels decrease as dietary fiber increases [17,19,[34][35][36][37]. Dietary fiber may also influence estrogen levels through its regulation of body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increasing dietary fiber has been suggested as a strategy for breast cancer prevention. Several intervention trials, in women with and without breast cancer, have shown that increasing dietary fiber results in lower serum estrogen levels [17][18][19], although some have found the association modest or nonexistent [20]. The effect of dietary fiber on androgens, SHBG, insulin-related peptides, and leptin is less clear, particularly among women with a previous breast cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%